Protecting the Wife’s Rights in Marriage as Reflected in Pre-nuptials and Marriage Contracts from the Cairo Genizah and Parallel Arabic Sources - Ashur, Amir (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2011)
The Cairo Genizah Collection contains marriage contracts, ketubot, gittin and divorce agreements, as well as a considerable amount of Halachic materials, relating to different aspects of marriage life. These rich, extremely rare materials, are unique sources for the study of Jewish family life in Medieval Egypt. Genizah society would compose prenuptial agreements containing the conditions that would apply to wedded couples during their marriage. This article deals with prenuptial agreements found among the Genizah documents, from which we can learn about the measures taken by the Genizah society to protect women from the inappropriate behavior of their husbands. The article particularly focuses on agreements that include distinct conditions aimed at protecting the rights of women within the nuclear family (ways of conduct, monogamy, living arrangements, and restrictions of freedom of movement of the couple). The Genizah documents further provide an important source for the study of the daily life of Muslims among which Jews had lived. The article compares Jewish marriage agreements with equivalent Arab agreements (Muslims and Coptic), mainly from the 11th to the 13th centuries. Both societies - Jewish and Arab - faced similar problems regarding women’s roles within the family. A comparison of the sources points to the ways in which each society coped with these problems. Hence, it allows one to discern the similarities and differences regarding their attitudes to marriage and the role of women.